Evaluation of total abdominal hysterectomy over the decade in Holy Family Red Crescent Medical College Hospital - A retrospective observational study - Nazneen, Rumana; Monir, Fahmida; Yeasmin, Salma; Akhter, Sharmin; Bakshi, Lipy; Sultana, Kishwar (Bangladesh Medical Journal, 2016)
Hysterectomy is the commonest major surgical procedure in Gynaecology & usually performed to improve quality of life rather than to cure life-threatening conditions. The rates differ between countries depending on differences in morbidity, health economical aspects, traditions and attitudes. This retrospective observational study was carried out from 2001-2010 & included all cases of abdominal hysterectomy done for benign and non emergency conditions in the department of Obstetrics & Gynaecology, Holy Family Red Crescent Medical College and Hospital, Dhaka with the intention to assess the proportion and the indications of total abdominal hysterectomy over a 10-year period. Percentage of the total abdominal hysterectomy remained between 50-70% of the total major operations over the decade. Fibroid was found to be the most common indication among the admitted patients (around 36%) with highest percetage in 2006 and 2007 (43% and 46% respectively). Next important indication was dysfunctional uterine bleeding (20%) followed by pelvic inflammatory disease (13%), ovarian mass (5%), endometriosis & adenomyosis (4%) and post menopausal bleeding (2%). The majority of hysterectomies were abdominal and the most common indication was uterine fibroids. The overall rate for hysterectomy remained reasonably stable. Bangladesh Med J. 2015 May; 44 (2): 87-91